Buccolingual root dimension of permanent mandibular canines as a complementary estimator of sex: a pilot study [Dimensão bucolingual da raiz dos caninos mandibulares permanentes como um estimador complementar do sexo: um estudo piloto] - De Koninck, A (2021)
Objective: To evaluate the potential of the buccolingual dimension of the permanent mandibular canine roots as a sex estimator, using midsagittal cone-beam computed tomography images. Methods: In this retrospective study, 58 Portuguese patients (27 female and 31 male) aged 18-60 years were assessed. The maximum buccolingual dimension of the cervical root was measured in the midsagittal plane through cone-beam computed tomography images. The Bland-Altman method was applied for the reliability analysis, and a receiver operating characteristics (ROC) curve was obtained for accuracy analysis. Results: The buccolingual root dimension on the mandibular canine showed statistically significant differences between sexes (t56 df = 4.871; p<0.0005). The optimal cut-off to differentiate males from females was 6.64 mm. The area under the curve (AUC) was 83.5% (p<0.0005). An overall accuracy of 79% was obtained. The percentage of males correctly estimated was 77.4%, compared to 81.5% of females. Conclusions: Our data suggest that canines’ buccolingual root dimension can serve as a complementary tool for sex estimation in a forensic context.